PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL MEDIASI (Studi pada Nasabah Bank Jateng Cabang Pembantu Kerjo) - Pramono, Yusuf Triwiyadi (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
The research was conducted at Kerjo Sub-Branch Bank Jateng. The population in this study is Bank Jateng Customer Employment Branch, which amounts to 1,264 customers. The sample used was 10% of the total population of 126. The sampling technique was purposive sampling, and accidental sampling. The technique of collecting data uses a closed questionnaire with a Likert scale of 5 (five) points. To prove the hypothesis, Path Analysis is used, while Sobel Test is used to test the mediating variable. The results of the study prove that: service quality variables have a significant effect on customer satisfaction of Kerjo Sub-Branch Bank, the corporate image variable has a significant effect on customer satisfaction of Kerjo Sub-Branch Bank Jateng customers, customer satisfaction variables have a significant effect on Kerjo Bank Branch customer loyalty, service quality variables significant effect on customer loyalty of Kerjo Branch Bank Central Java Bank, corporate image has a significant effect on customer loyalty of Kerjo Branch Bank Jateng, customer satisfaction is able to mediate the effect of service quality on customer loyalty, and customer satisfaction is not able to mediate the influence of corporate image on customer loyalty.